PERCEPTIONS OF ENGLISH TEACHERS’ IN INTERACTIVE COMPUTER-BASED MEDIA TO ASSIST VOCABULARY ACHIEVEMENT OF MILLENNIAL STUDENTS - Faindah, Nur; Azis, Awalia; Qalbi, Nur (FKIP Unismuh Makassar, 2023)
This study aims to find out the perceptions of English teachers regarding the use of computer-based interactive media to improve students' vocabulary achievement. the method used in this research was qualitative method in the type of descriptive research. this research used an observation checklist and interview as instruments to collect the data. the subject in this research were English teachers who taught in high school with 2 English teachers. this research used purposive sampling technique.Based on the results of the study, the teacher's perception of interactive computer-based media gave positive answers, the use of interactive computer-based media can really help teachers in the learning process. The teacher is greatly helped by the existence of computer-based media because it can help explain the material displayed. Showing videos, PowerPoint, or songs can train students to acquire new or difficult vocabulary. Students can learn and improve their vocabulary by practicing and practicing it in their daily lives. the effectiveness of computer-based media can help all elements of students' soft skills, in the form of increasing vocabulary, reading, writing, and listening. Using the media makes students feel motivated and not bored during the learning process.